Urban waste and agriculture: a win-win for farmers and for the city? - Drechsel, Pay (2022)
The reuse of usually free waste resources in urban and peri-urban farming is a common reality but serves primarily the farming community, and only indirectly the waste or sanitation service chain, or the consumer. Resource recovery scaling appears thus only likely in smaller towns surrounded by agriculture. Financial cost recovery continues to be a key issue for public and private entities. Returns on investing can vary widely, but seem unlikely to drive large improvements in sanitation or waste management unless entrepreneurs are provided with an opportunity to monetize the economic benefits for society and for nature, benefits which are fully internalized by society but usually lack a direct market value.